Historic Insect Losses in Kansas Cotton and Observations from Finney County - Anthony Zukoff (Kansas Agricultural Experiment Station Research Reports, 2024)
Twenty years of insect data from Kansas cotton production illustrated the variety of pests that can cause significant yield loss. During a typical growing season, a producer can expect three to five species to need control measures. Thrips, cotton fleahoppers, and lygus bugs are of the most concern; however, losses due to bollworm are steadily increasing following years of control with Bt cotton. No control measures were needed during the 2021 growing season in cotton research plots in Finney County; however, most major pest species were observed along with some species of occasional concern.
Keywords: cotton; Kansas; insects; bollworm; lygus; thrips; fleahopper; resistance